PREVALENSI PIROPLASMOSIS PADA SAPI DI KABUPATEN POHUWATO - Nugroho, Tri Ananda Erwin; Graselawati, Graselawati (Gorontalo Journal of Equatorial Animals, 2024)
This study aims to determine the incidence of Piroplasmosis in cattle in Pohuwato. This study aims to determine the incidence of Piroplasmosis in cattle in Pohuwato Regency. The sample used was cow's blood taken from the jugularis vein with a total of 100 blood samples. Blood sampling was carried out randomly proportionally in each sub-district in Pohuwato Regency. Blood examination uses a thin blood smear examination method. Based on examination using a binokuler microscope with a magnification of 1000. From the result of examination of 100 blood samples, 24 cattle blood samples had piroplasmosis.Keywords: Piroplasmosis, blood, cattle, Pohuwato, Gorontalo